Investigation of yield and quality parameters of some sugar beet varieties in Muş ecological conditions - Yağmur, Hanifi; Yaşar, Mustafa (My University, 2023)
In plant production, determining the suitable varieties suitable for the location and choosing the varieties with the best performance are among the top priorities. Biplot analysis has become widespread in recent years as an important statistical technique for plant breeders and those working in agricultural research. This study was carried out according to Randomized Complete Block Design with 18 upcountry and 2 abroad registered varieties in Muş location in 2022 year. Yield and quality components were investigated. According to the results of variance analysis, it was determined that there were statistically significant differences at the level of 1% among the varieties in terms of all the traits examined. According to the average data obtained in the study; bifurcation varied between (%) 5.4-17.8, leaf yield 13.54-24.28 t ha-1, root yield 73.42-93.57 t ha-1, biological yield 90.29-118.26 t ha-1, sugar content (%) 16.2-19.0, plant juice purity 82.39- 88.10%, dry matter (%) 16.4-20.1, ?-amino N (mg 100g-1) 0.0405-0.0498 and ash (%) varied between 2.49-3.35. According to the results of the research, in terms of root yield, G10 no and G14 no varieties came to the fore in terms of the most stable and examined traits. G12 no variety came to the fore in terms of sugar yield and G19 no variety in terms of sugar content. When the average data of all examined traits are evaluated together, G10, G11 and G14 no varieties are considered as the most stable varieties. However, varieties with high root yield, sugar content and sugar yield are the primary preferences of growers in sugar beet production. When all the data of the varieties used in the research are evaluated together; G2, G4, G8, G10, G11, G12, G14, G15 and G19 no varieties can be recommended for Muş ecological conditions. However, it was concluded that the study should be carried out in the following years for more decisive recommendations.